Household carbon dioxide emissions Engel Curve dynamics. - Huang, Robert; Kahn, Matthew E. (Contemporary Economic Policy, 2024)
Household carbon dioxide emissions depend on the household's attributes and location. Wealthier suburbanites drive more and consume more energy at home. In recent years, affluent individuals have been more likely to purchase electric vehicles and install solar panels. Using several datasets from California, we observe that these shifts in consumer behavior have flattened household Carbon Emissions Engel Curves in the transportation sector and the electricity sector. Based on voting data from a 2018 proposition to repeal a fuel tax in California, we document that communities tend to support higher fuel taxes when their vehicle fleet is more fuel‐efficient.